Investigation of coronavirus anxiety and caregiving burden among the parents of children with cancer during the COVID‐19 outbreak: A descriptive and cross‐sectional study. (24th April 2022) - Bekar, Pınar; Erkul, Münevver; Efe, Emine
Abstract: Objective: This study aimed to investigate the coronavirus anxiety and caregiving burden of parents of children with cancer during the COVID‐19 outbreak. Methods: This descriptive and cross‐sectional study, including 136 parents of children with cancer, was administered through an online survey at a university hospital from 1 to 31 January 2021. Participants completed a questionnaire form, the Zarit Caregiver Burden Scale and the Coronavirus Anxiety Scale. Results: This study identified a significant difference in the caregiving burden scores of parents according to whether their relatives had been diagnosed with COVID‐19, whether they were exposed to coronavirus in their environment and whether their children had other illnesses. A significant difference in the coronavirus anxiety scores of parents was observed according to their child's sex and the time elapsed since their child's cancer diagnosis. No correlation was identified between the Zarit Caregiver Burden Scale scores and the Coronavirus Anxiety Scale scores. Conclusion: Oncology nurses and other health professionals should be aware of and consider the factors that influence the caregiving burden and coronavirus‐related anxiety experienced by parents of children with cancer during the COVID‐19 outbreak.